Development And Evaluation Of A Gastroretentive Drug Delivery System For Thiamine Hydrochloride - Kam, Li Ying (2013)
A gastroretentive tablet system was developed and evaluated for the oral delivery of thiamine hydrochloride as the model drug with an absorption window. A simple, specific and sensitive liquid chromatographic tandem mass spectrometric method was first developed for studying the oral bioavailability of thiamine hydrochloride using rats. It was found that the oral bioavailability of thiamine was poor and erratic, but the poor bioavailability was not attributed to stability problem in the gastrointestinal tract. Rather, it was due to its restricted absorption in the upper region of the small intestine. The oral bioavailability of thiamine was also found to be influenced by CYP3A4 and P-glycoprotein (P-gp).